HUKUM TATA NEGARA DALAM KEADAAN DARURAT PENANGANAN COVID-19 PERSPEKTIF SIYASAH DUSTURIYAH : (Studi Kasus Pemerintah Kota Makassar) - Amatullah,; Kurniati,; Rahman, Arif (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The purpose of this study is to describe the implementation of policies in emergencies carried out by the government in terms of handling Covid-19 in Makassar City, the views of siyasa dusturiyah regarding constitutional law in emergencies in handling Covid-19. Regarding the abnormal (emergency) state of the country, appropriate actions can be based on ordinary law because the ordinary legal system cannot be applied as it should, to deal with the situation during the Covid-19 pandemic. This research is a field research using a Normative Syar'i approach and an Empirical juridical approach. Based on the results of this study, following the central government's stipulation regarding the Covid-19 pandemic emergency policy from several issued regulations such as Large-Scale Social Restrictions (PSBB), health quarantine and social assistance for the community, the Makassar City government implemented The policy stipulations are in accordance with central government policy regulations. In the siyasa dusturiyah perspective in implementing the functions and functions and authority of the state, the government in carrying out its duties as a state administration official is tasked with making a policy to realize the benefit of the community